Dynamics of first-time patenting firms - Øivind Anti Nilsen; Arvid Raknerud (Statistics Norway, Research Department, 2022)
This paper investigates firm dynamics in the period before, during, and after an event consisting of a first published patent application. The analysis is based on patent data from the Norwegian Industrial Property Office merged with data from several business registers covering a period of almost 20 years. We apply an event study design and use matching to control for confounding factors. The first patent application by a young firm is associated with significant growth in employment, output, assets and public research funding. Moreover, our results indicate that economic activity starts to increase at least three years ahead of the first patent application. However, we find no evidence of additional firm growth after patent approval for successful applicants. Our findings indicate that the existence of a properly functioning patenting system supports innovation activities, especially early in the life cycle of firms.
Keywords: C33; D22; O34; 330; Patenting; Firm performance; Panel data; Event study design